Maternal Mortality and Referral Status in Chonburi Hospital: 16 Years (1996-2011) Experience - Teerapat Chullapram (The Royal Thai College of Obstetricians and Gynaecologists, 2012)
Objective: To assess the cause of maternal death and maternal mortality ratio in Chonburi HospitalMaterials and Methods:All maternal deaths in Chonburi Hospital from January 1996 to December 2011 were included. Data from the department and the hospital medical records was review.Results:Total maternal mortality ratio (tMMR, total = referred cases plus Chonburi Hospital own cases) and Chonburi Hospital maternal mortality ratio (CHMMR, Chonburi Hospital own cases) was 52.4 and 13.4 per 100,000 live births, respectively. The tMMR rate seemed unchanged from tMMR during 1982-1991. However, the figure for all 47 deaths was exaggerated because there were added referred maternal deaths without added corresponding live births. Most of the maternal deaths (74%) were referred cases. Most deaths (63.8%) were direct maternal deaths. Five most common causes of deaths were postpartum hemorrhage (PPH), amniotic fluid embolism (AFE), heart diseases, pregnancy-induced hypertension (PIH) and abortion/ectopic pregnancy-related. For Chonburi Hospital cases, most common causes of death were AFE, heart diseases and PIH. Most of the referred cases, 74.3%, arrived at Chonburi Hospital in seriously ill condition. Eight cases (22.9%) arrived hopelessly (post cardiac arrest or cardiac arrest on admission, brain death or moribund condition). Many deaths were obviously or possibly preventable especially in category of PPH and abortion/ectopic pregnancy-related deaths. Conclusion:Our own CHMMR was 13.4 per 100,000 live births and comparable with that of the developed country. Our tMMR, though a bit exaggerated, was the same as other developing country MMR. There is the opportunity for improvement as many deaths were preventable.